Renal Cell Carcinoma Dwelling Upon a Renal Cyst Wall and Laparoscopic Management - Özgök, Ya?ar; Ate?, Mutlu; Ho?can, Mustafa Burak; ?stanbulluo?lu, Okan; Ba?al, ?eref; Zor, Murat (Urology Journal, 2014)